ANALISIS PEMBIAYAAN PENDIDIKAN MENENGAH DI KABUPATEN GOWA - Perdana, Novrian Satria (JURNAL NALAR PENDIDIKAN, 2019)
Education as a core activity of HR development has proven to have a significant contribution to economic benefits. In order to fund the cost of education, especially to quality secondary education, it is necessary to know in advance how much funding is needed and where the funding sources are obtained. Based on the description, the purpose of this study is to calculate the cost of non-personnel operating unit costs and its fulfilment strategies in the implementation of quality secondary education. The sample of this study amounted to 10 schools consisting of 4 high schools and 6 public vocational schools in Gowa Regency, South Sulawesi Province in 2018. Based on the results of the study, it was concluded that the non-personnel operational costs at the high school level were obtained by variations in non-personnel operational unit costs (BONP) ranging from Rp. 735,000. IDR 3,850,000 per student per year. And the sample BONP of Vocational High School shows quite a high variation, which is around Rp1,845,000. Rp.4,429,000 per student per year. The amount of the funds, the average use of the non-personnel operational costs budget in the highest SMA is used for minor maintenance and repairs (51%). Whereas for Vocational Schools, the largest average budget for non-personnel operational costs at Vocational Schools is used for minor maintenance and repairs (74%).